The Role of Language in Influencing International Tourism Demand in ASEAN+3 Countries - Fung-Thai, Thien (Universiti Malaysia Sarawak (UNIMAS), 2022)
This thesis empirically examined the tourism demand for the ASEAN+3 countries, namely Brunei, Cambodia, China, Indonesia, Japan, Korea, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand and Vietnam from macroeconomic perspective. The static linear panel model analysis was applied to examine the influence of tourists’ income, destination countries income, distance, free trade agreement, adjacent country, tourism price and language towards tourism demand in these countries. Tourism sector is vulnerable to external shocks, therefore, ASEAN+3 governments need to identify determinants of tourism demand to fully utilise their resources and efforts in sustaining the development of tourism sector in these countries. The results obtained in this study showed that tourist income, distance, adjacent country, tourism price and language are more influential determinants while the effect of destination income and free trade agreement are relatively less significant. Identification of these determinants allow governments of ASEAN+3 countries to design individual policy and also establish collaboration among each other to strengthen tourism sector performance.